Integrated HTML and CSS : - DeBolt, Virginia (SYBEX, 2005)
Almost all web designers use Cascading Sheets to control the presentation of the websites they construct out of HTML. Why learn one and then the other when you can just as easily—and much more effectively—learn both at the same time? This book's integrated approach speeds your progress and leaves you with a stronger, more cohesive set of skills.